Faktor-faktor yang mempengaruhi persepsi pekerja terhadap Sarawaknet - Noor Afizah, Razali (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This research aims to study the factors affecting the employees' perception, towards Sarawaknet in public sector. Research sample of this study involves 85 respondents, which consists of government servants. This research presents ten null hypotheses to determine the relationship between factors affecting the perception toward Sarawaknet. Several statistical methods were used based on their suitability with the hypothesis by using Statistical Package for Social Sciences (SPSS) version 11.0. Based on descriptive statistic, if was found that the employees ' perception towards Sarawaknet is generally moderate. Hypothesis testing on Ho1 (gender), Ho2 (age), and Ho3 (experiences in using WAN application) yielded no Significant difference between perceptions of employees' towards Sarawaknet. This research also finds that H04 (effectiveness), Ho5 (efficiency), Ho6 (visual engaging), Ho7 (error-tolerant), Ho8 (easy to learn), Ho9 (problem faced), and Ho10 (employees ' acceptance) were found to have significant relationship with perception of employees towards Sarawaknet with effectiveness (r=0.562, p<0.01), efficiency (r=0.492, p <0.01), visual engaging (r=0.364 , p <0.01), error-tolerant (r=0.3l8, p <0.01), easy to learn (r=0.409, p<0.01), problem faced (r=0.287, p<0.01), employees ' acceptance (r=0.655, p<0.01). Overall, this research shows that demographic variables do not affect employees' perception towards Sarawaknet. However. factors such as effectiveness, efficiency, visual engaging, error-tolerant, easy to learn, problem faced, and employes' acceptance were found to have influence in shaping [he perception of employees towards Sarawaknet. The implications of this research shows that related factors should be given full attention to retain the employees' perception towards Sarawaknet in present and enhance the employees ' perception towards Sarawaknet in future.